Children with Covid-19 in Pediatric Emergency Departments in Italy - Parri, Niccolò; Lenge, Matteo; Buonsenso, Danilo (The New England journal of medicine, 2020)
This letter describes a cohort of 100 children younger than 18 years of age with RT-PCR–confirmed Covid-19 who were assessed in 17 pediatric emergency departments in Italy. The descriptive results are compared with previously published results involving children in China and the United States.